Mechanisms of Neurodegeration in Type 2 Diabetes and the Neuroprotective Potential of Dipeptidyl Peptidase 4 Inhibitors - Matteucci, E.; Giampietro, O. (Current Medicinal Chemistry, 2015)
Prospective epidemiological studies suggest that type 2 diabetes is a risk factor for neurodegenerative pathologies such as Alzheimer disease, vascular dementia, and Parkinson disease. Drugs that act as incretin receptor agonists or inhibit the proteolytic degradation of incretins (dipeptidyl peptidase 4 inhibitors) have been approved since 2005 for use in diabetes treatment. Dipeptidyl peptidase 4 (DPP4) cleaves N-terminal dipeptides from polypeptides when the second residue is proline, hydroxyproline, dehydroproline or alanine. The inhibition of DPP4 hydrolytic activities extends the halflife of these peptides by preventing their degradation. Several peptides have been identified as DPP4 substrates, including neuropeptides, chemokines, and the incretin hormones; hence the pleomorphic effects of DPP4 inhibition. Recently, the neuroprotective properties of these drugs have been evaluated in cell cultures and animal models, not yet in human trials. Although mechanisms distinct from glycaemic control alone have been claimed to account for protection against neuronal degeneration, the precise cellular mechanism by which DPP4 inhibitors exert their neuroprotective effects remain unknown. The present review is focused on the candidate pathways that could be involved in mediating DPP4 inhibitors-mediated protection against neuronal degeneration.
Keywords: Alzheimer disease